2011
DOI: 10.1038/jid.2011.221
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-Releasing Hormone Selectively Stimulates Human Hair Follicle Pigmentation

Abstract: In amphibians, thyrotropin-releasing hormone (TRH) stimulates skin melanophores by inducing secretion of α-melanocyte-stimulating hormone in the pituitary gland. However, it is unknown whether this tripeptide neurohormone exerts any direct effects on pigment cells, namely, on human melanocytes, under physiological conditions. Therefore, we have investigated whether TRH stimulates pigment production in organ-cultured human hair follicles (HFs), the epithelium of which expresses both TRH and its receptor, and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 55 publications
(143 reference statements)
1
37
0
Order By: Relevance
“…TRH stimulated hair shaft formation, prevented apoptosis, increased proliferation of hair matrix keratinocytes and prolonged the anagen phase of hair growth cycle (Gaspar et al, 2010, van Beek et al, 2008). TRH can also stimulate hair follicle pigmentation (Gaspar et al, 2011), probably by direct activation of melanocortin type 1 receptor (MC-1R), confirming our previous hypothesis (Slominski et al, 2005b, Slominski et al, 2002e). It was shown that TSH acting via TSH-R1 receptor increased cAMP production by human keratinocytes, human and hamster melanoma cells ((Slominski et al, 2002e) and enhanced the proliferation of epidermal keratinocytes and dermal fibroblasts (Bodo at al., 2010).…”
Section: Equivalent Of Hypothalamic-pituitary-thyroid (Hpt) Axissupporting
confidence: 87%
“…TRH stimulated hair shaft formation, prevented apoptosis, increased proliferation of hair matrix keratinocytes and prolonged the anagen phase of hair growth cycle (Gaspar et al, 2010, van Beek et al, 2008). TRH can also stimulate hair follicle pigmentation (Gaspar et al, 2011), probably by direct activation of melanocortin type 1 receptor (MC-1R), confirming our previous hypothesis (Slominski et al, 2005b, Slominski et al, 2002e). It was shown that TSH acting via TSH-R1 receptor increased cAMP production by human keratinocytes, human and hamster melanoma cells ((Slominski et al, 2002e) and enhanced the proliferation of epidermal keratinocytes and dermal fibroblasts (Bodo at al., 2010).…”
Section: Equivalent Of Hypothalamic-pituitary-thyroid (Hpt) Axissupporting
confidence: 87%
“…Silencing of core clock components PER1 or BMAL1 increases melanin content in human anagen VI HFs in a hair cycle-independent manner Previously, we had observed that clock gene silencing appeared to increase the melanin content of human HFs (Al-Nuaimi et al, 2014). Therefore, utilizing Masson-Fontana histochemistry for visualizing melanin in BMAL1 or PER1 knock-down HFs we analyzed whether the increase in pigmentation simply reflects the anagen-prolonging effects of gene silencing (Kloepper et al, 2010;Gáspár et al, 2011;Samuelov et al, 2013;Al-Nuaimi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, environmental endocrine disruptors may likewise target the cutaneous neuroendocrine network and not only classical endocrine organs. With regard to the most commonly associated autoimmune disease of vitiligo, thyroid disease, it is intriguing that the majority of hypothalamic‐pituitary‐thyroid axis related genes are autonomously expressed in human skin with some of the them even directly controlling melanin biosynthesis . Furthermore, the adverse effect of ROS accumulation on autoimmunity might be increased by the potential immunotoxic effect that some environmental pollutants and chemical agents have .…”
Section: Introductionmentioning
confidence: 99%